PENGARUH PENAMBAHAN BETA KAROTEN DALAM PENGENCER TRIS KUNING TELUR TEHADAP KUALITAS SEMEN CAIR KERBAU LUMPUR (SWAMP BUFFALO): EFFECT OF BETA CAROTENE ADDITION IN EGG YOLK TRIS DILUENT ON THE QUALITY OF LIQUID SEMEN OF SWAMP BUFFALO - Yani, Nadila Fitri; Elisia, Rini; Maiyontoni, Maiyontoni; Komala, Refika; Meidita, Fadilla (Universitas Boyolali, 2025)
Efforts to improve the quality of frozen semen of swamp buffalo have always been made, one way is by adding an ingredient that is effective in protecting sperm during the process of dilution, freezing and thawing as a compound that can neutralize free radicals (antioxidant). One antioxidant that has been widely studied is beta carotene (?-Carotene). This natural pigment has the ability to stabilize cell membranes, protect DNA, and reduce oxidative damage to sperm cells. The purpose of this study was to determine the effect of ?-carotene addition in egg yolk Tris diluent on the quality of liquid semen of swamp buffalo. The research materials used consisted of artificial vagina, microscope, Computer Assisted Semen Analysis (CASA), object glass, cover glass, citrate, egg yolk, eosin-nigrosin dye and fresh semen of four-year-old swamp buffalo collected weekly at BIB Tuah Sakato, Payakumbuh. The experimental research method used a completely randomized design with four treatments and five replicates. The treatment of adding ?-Carotene into egg yolk tris (TKT) concentration: 0, 0.1, 0.2, and 0.3% which was equilibrated for 3 hours. Variables observed in this study include mortality, viability and abnormality of liquid semen. The results showed the addition of ?-carotene in egg yolk Tris (TKT) diluent at concentrations of 0%, 0.1%, 0.2%, and 0.3% showed no significant effect on motility, viability, and abnormality of swamp buffalo spermatozoa (P > 0.05). The highest mean motility was recorded at 0.1% concentration (80.12 ± 3.95), followed by 0% (76.54 ± 6.48), 0.2% (76.48 ± 5.59), and 0.3% (73.65 ± 4.88). Viability was also highest at 0.1% (68.22 ± 5.41), then 0% (66.88 ± 6.33), 0.2% (64.94 ± 6.11), and 0.3% (61.51 ± 8.08). The lowest abnormality was found at 0.3% (30.50 ± 4.58), then 0.2% (31.45 ± 2.63), 0.1% (34.23 ± 2.22), and 0% (34.51 ± 2.49). Although not statistically significant, 0.1% concentration produced the highest motility and viability, so it can be considered added in TKT diluent.